KEPENTINGAN INDONESIA BEKERJASAMA DENGAN JEPANG DALAM BIDANG PERTAHANAN TAHUN 2015 - Oki Rilo Nainggolan; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to explain the interests of Indonesia in cooperation with Japan in the field of defense in 2015. The agreement is set forth in a Memorandum of Understanding on cooperation and exchange in the field of defense on March 23, 2015 in Japan. The agreement was signed by the Minister of Defense of the Republic of Indonesia Ryamizard Ryacudu and Japanese Defense Minister Gen Nakatani.In this research, the author used national interest concept and the theory of foreign policy strategic model / rational model and the theory of international cooperation by Kalevi Jaako Holsti. This research used qualitative research that attempt to express an essence of social phenomena by analyzing the phenomenon based on existing theories and data. Data collection techniques from this research is library research where the data comes from books, newspapers, journals, official documents, internet and other data that support in writing this research.The result of this research is the cooperation between Indonesia and Japan in the field of defense in 2015 aims to meet the needs of Indonesia in improving its defense in terms of quality and quantity through modernization of Indonesia’s defense equipment, Transfer of Technology, information exchange on defense matters, exchanges and training of personnel, And experts, and other forms and the fulfillment of Minimum Essential Force Phase II can be met maximally. Indonesia's desire to become a maritime axis of the world is also increasingly realized and make Indonesia's defense industry more independent with the cooperation.Keywords: Jakarta Declaration, International Relations, National Interest, Defense Cooperation, Modernization of Defense Equipments.